Agricultural Insurance in India - K. B., Nidheesh (Indian Journal of Finance, 2010)
Agriculture productions in India are habitually precious due to their vulnerability to natural calamities such as droughts, floods, cyclones, storms, landslides and earthquakes. Vulnerability of agriculture to these calamities is compounded by the eruption of pandemics and man-made disasters such as fire, sale of unauthentic seeds, fertilizers and pesticides, price crashes etc. All these events rigorously affect farmers as there is failure in production and loss of farm income. With the emergent commercialization of agriculture, the enormity of loss due to adverse eventualities is increasing. The question is how to guard farmers by minimizing such losses. For a segment of farming society, the minimum support prices for definite crops provide a measure of income stability. But for most of the crops and in most of the states, MSP is not realized. In recent times, means like contract farming and future trading have been established which are anticipated to provide some insurance against price oscillations directly or indirectly. But agricultural insurance is an important mechanism to effectively address the risk to harvest and income resulting from various natural and manmade occurrences. Agricultural Insurance is a way of shielding the agriculturist against financial losses occurring due to agricultural losses arising from named or unexpected hazards beyond their control (AIC, 2008).